Homothallism, morphology and phylogenetic position of a new species of Sellaphora (Bacillariophyta), S. pausariae - David G Mann; Aloisie Poulíčková (Plant Ecology and Evolution, 2019)
Background and aims – The eutrophic Blackford Pond in Edinburgh has already provided the holotypes of six other Sellaphora species. A further undescribed species is present and requires description and characterization.Methods – Clones of the new species are characterized by light (LM) and scanning electron microscopy (SEM) and molecular phylogenetics (from a concatenated five-gene alignment of 18S rDNA, 28S rDNA, 23S rDNA, cox1 and rbcL, and a two-gene alignment of cox1 and rbcL).Key results – Sellaphora pausariae sp. nov. is named in honour of Dr Eileen Cox (‘pausaria’ = a lady coxswain). In molecular phylogenies, small-celled Sellaphora species (‘minima’ and ‘seminulum’ morphologies) branch off at the base of Sellaphora, though nodes are not well supported. Species and demes previously classified in either “Navicula pupula” or “Navicula bacillum” group into three very well supported clades (numbered 1–3). Although appearing in LM and SEM like a smaller, more delicate version of S. obesa, S. pausariae (clade 1) is not closely related to S. obesa (clade 2). Features of Sellaphora pausariae not confirmed previously in any Sellaphora but possibly widespread are: (a) hymenes with pores arranged in a regular scatter; (b) a stepped mantle near the poles; and (c) a ‘primodominant’ girdle comprising a wide band 1, a segmental band 2, and two extremely thin bands at the abvalvar end of the girdle. Sellaphora pausariae is homothallic; a deficiency of interclonal pairings in two-clone mixtures is interpreted as reflecting the tendency of cells to mate with their immediate neighbours.Conclusions – Morphologically, the new species can be differentiated from existing described species, though only problematically from some informally named demes. Molecularly, it is clearly characterized by the five genes sequenced. Girdle terminology needs expansion (e.g. to distinguish primodominant girdles from ‘graded’ ones, in which the bands gradually decrease in width and structural complexity from the valve outwards).